INFLATION ACCOUNTING ASSESSMENT OF RELEVANCE FINANCIAL REPORT AT. Astragraphia, TBK - One, Wigiyanti; Kholisoh, Dr. Luluk (Accounting, 2009)
An example of state-owned Indonesian company to calculate an inflation shock of inflation accounting, the need to know The main purpose of its financial statements and the economy of a developing country is the low level of inflation, but the problems often faced by countries developed is the high rate of inflation, causing the economic crisis. While the accounting records in Indonesia are generally embraced Historical Cost, where these concepts do not know of any such changes influence inflation of stable monetary unit that resulted in all transactions that occurred recorded on the basis of historical value or the value obtained during a transaction. Goal research to find out how to make financial reports to include elements know the size of the effect of inflation and the inflation factor to the report finance was beneficial or detrimental to the internal party. Now results showed that PT. Astragraphia, Tbk in December 2007 and 2008 in calculating the financial statements using the price index consumer (CPI) there were significant differences in outcome results This company gained a slight loss or decreased profits. Keyword : inflation, financial report